2004
DOI: 10.1083/jcb.200307164
|View full text |Cite
|
Sign up to set email alerts
|

MuSK is required for anchoring acetylcholinesterase at the neuromuscular junction

Abstract: At the neuromuscular junction, acetylcholinesterase (AChE) is mainly present as asymmetric forms in which tetramers of catalytic subunits are associated to a specific collagen, collagen Q (ColQ). The accumulation of the enzyme in the synaptic basal lamina strictly relies on ColQ. This has been shown to be mediated by interaction between ColQ and perlecan, which itself binds dystroglycan. Here, using transfected mutants of ColQ in a ColQ-deficient muscle cell line or COS-7 cells, we report that ColQ clusterizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 47 publications
(69 reference statements)
4
127
0
5
Order By: Relevance
“…As such, antibodies that inhibit MuSK function would be expected to disrupt the architecture of the neuromuscular synapse as well as perturb neurotransmitter release and reception (9,18,19,34,(41)(42)(43)(44). Because the synaptic accumulation of acetylcholinesterase (AChE), like all other postsynaptic proteins, depends on MuSK (10,42), IgG4 antibodies to MuSK are likely to lower AChE expression at the synapse, which may explain the hypersensitivity of MuSK MG patients to AChE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…As such, antibodies that inhibit MuSK function would be expected to disrupt the architecture of the neuromuscular synapse as well as perturb neurotransmitter release and reception (9,18,19,34,(41)(42)(43)(44). Because the synaptic accumulation of acetylcholinesterase (AChE), like all other postsynaptic proteins, depends on MuSK (10,42), IgG4 antibodies to MuSK are likely to lower AChE expression at the synapse, which may explain the hypersensitivity of MuSK MG patients to AChE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…First, the collagen domain harbors two heparan sulfate proteoglycan (HSPG) binding domains (Deprez et al, 2003) that bind to HSPG, such as perlecan (Peng et al, 1999). Second, the C-terminal domain binds to MuSK (Cartaud et al, 2004).…”
Section: Endplate Ache Deficiency Due To Defects In Collagen Qmentioning
confidence: 99%
“…Another possible ColQ-protein interaction has been described by Cartaud and colleagues [17] who suggested that the putative agrin receptor MuSK is also a receptor for ColQ-AChE and was required for AChE binding to the neuromuscular junction. Using a ColQ-GFP fusion protein expression to emulate expression of ColQ-AChE, and co-transfection with MuSK, the authors demonstrate that the surface clusters of ColQ-GFP co-distribute with endogenous perlecan and exogenous MuSK in COS-7 cells.…”
Section: Localizing Ache To the Neuromuscular Junctionmentioning
confidence: 99%